Differential diagnosis and laparoscopic resection of an adrenal pseudocyst: A case report. (2020) - Yokoyama, Yuichiro; Tajima, Yusuke; Matsuda, Izuru; Kamada, Kentaro; Ikehara, Takashi; Uekusa, Toshimasa; Momose, Hirokazu; Yoneyama, Satomi; Sakata, Hiroki; Hidemura, Akio; Suzuki, Hiroyuki; Ishimaru, Masahiro
Highlights: Adrenal pseudocysts are infrequent entities. The preoperative diagnosis of left adrenal pseudocysts is sometimes difficult. Laparoscopic surgery is useful as an adrenal cyst intraoperative diagnostic tool. Abstract: Background: Adrenal pseudocysts are infrequent entities and definite preoperative diagnosis is difficult. We present a case of left adrenal pseudocyst, which was intraoperatively identified as having an adrenal origin and was resected using a laparoscopic approach. Presentation of case: A 41-year-old female was referred to our hospital for examination and treatment of a cystic lesion in the pancreatic tail. Preoperative diagnostic imaging studies showed a cystic lesion with intramural nodular structure, measuring 39 mm in the largest diameter and located between the pancreatic tail and the left adrenal gland. However, the origin of the cystic lesion remained unclear, and a definite preoperative diagnosis was not established. The cystic lesion was intraoperatively identified as having an adrenal origin after the division of the loose connective tissue layer around the lesion under the laparoscopic magnified view. Laparoscopic left adrenalectomy was performed as radical treatment and the histopathological diagnosis confirmed the presence of an adrenal pseudocyst. Discussion: We could not ascertain the origin of the cystic lesion from the left adrenal gland and establish a definite diagnosis based on the findings of the preoperative diagnostic imaging modalities. Laparoscopic surgery could be more advantageous than the conventional open approach as not only a minimally invasive treatment option but also as an intraoperative diagnostic tool for cystic lesions in the pancreatic tail. Conclusion: This case report suggests that laparoscopic surgery could be clinically useful as not only a minimally invasive treatment but also an intraoperative diagnostic tool for cystic lesions in the pancreatic tail region.